Tribotechnical Properties Lead Bronzes; Applied Mechanics and Materials; Vol. 379 : Innovation materials and manufacturing technologies, economic aspects in enterprises - Martyushev N. V. Nikita Vladimirovich (2013, 2013)
Title screen